Street trading,human rights and health issues: a study of young girls in Nigeria (1999)
The social practice of street trading now a problem is growing in Nigeria and it is attracting official attention. This cancerous social problem spreading to the urban cities in Nigeria has amongst its victims, children from ages seven and sometimes lower, hawking all kinds of items on and along major busy roads in Nigeria. Such children risk their lives and health, face vehicular and other dangers and constitute obstruction to vehicles. This paper identified poverty as the major cause of street trading. Other causes discussed include social causes such as the break down in the social institution like the family and school and political cases . The health implications discussed are sexual abuse, drug abuse and dependence, tiredness and fatigue, bad and unhygienic eating habit and vehicular accident. The Human Right implications include child exploitation, neglect and abuse. Finally, solution proffered includes legislative evaluation, publicity and awareness campaigns of the danger of street trading and the introduction of relevant educational policies.